Bold and stubborn: The experience of Agroecological Notebooks and the new challenges for Technical Assistance and Rural Extension in Bahia, Brazil - Jalil, Laeticia Medeiros; Silva, José Claudivam da; Freitas, Karine Pereira de; Siqueira, Ana Elizabeth Souza Silveira de; Cardoso, Elisabeth Maria; Oliveira, Maria do Socorro de Lima (International Journal of Advanced Engineering Research and Science, 2022)
The construction of experiences in which rural women are the protagonists comprises conflicting processes, since the patriarchal culture denies them this place and reiterates violent practices of invisibility and devaluation of their experiences. Access to public policies that make it possible to understand and strengthen rural women as a political subject promotes other dynamics of social life. Thus, this work presents the analysis of the use of agroecological notebooks (CAs), as an innovation in the technical advisory actions of the Pró-Semiárido Project (PSA/BA). The CA is a tool that makes it possible to qualify the Technical Assistance and Rural Extension (ATER) action, which requires a new institutional culture from organizations and transformations in the lives of rural women. Its use enables the construction of a process of strengthening autonomy and reflection on the importance of productive and reproductive work and contributes to breaking with inequalities that mark their lives and reduces their work as mere help.